Gender Salience and Recategorization of New Directors: The Role of Political Ideology - Chow, Dawn Yi Lin; Petrou, Andreas; Procopiou, Andreas (My University, 2023)
Pressure from stakeholders has resulted in increased board gender diversity. Such diversity, however, goes against the well-accepted concept of demographic homophily. In addition, other studies find that increased board gender diversity may not unequivocally lead to better firm decisions, which does not sit well with the assumption that demographic minorities bring diverse information/ideas to the board. This study advances an explanation for these inconsistencies in the literature by integrating symbolic management and recategorization theories to assert that boards outwardly conform to greater gender diversity, whilst choosing to reinforce value homophily by recategorizing female new directors based on shared political ideology. We test our hypotheses on a sample of 13,483 new director appointments in 2,473 US firms using fractional regression analysis. The findings show that the appointment of a new female director strengthens the association between the board's and the new director's political ideology. In addition, this relationship is strengthened when there is a female CEO, or when the new female director has a less similar demographic background. Moreover, supplemental analysis considering ethnic minority new director appointments shows similar results. The study makes important contributions toward the literatures on female new director selection, recategorization and political ideology. We shed light on why research is ambivalent regarding the benefits of gender diversity since findings show that boards compensate for gender diversity by becoming more homogeneous on political ideology, a value dimension that influences board decisions.
Keywords: corporate governance; diversity/gender; social identity theory; boards of directors